HYBRID 3D GRAPHENE-CARBON NANOTUBES ABSORBENT INTEGRATED WITH POLY(METHYL METHACRYLATE) AND POLYPYRROLE FOR ENHANCED OIL ABSORPTION - CHEEN, ONG CHONG (2020)
Oil removal via absorbent materials has been a simpler and cost-effective alternative for the past few decades.